Genomic expertise in action: molecular tumour boards and decision‐making in precision oncology. Issue 8 (13th June 2019) - Bourret, Pascale; Cambrosio, Alberto
Abstract: The recent development of cancer precision medicine is associated with the emergence of 'molecular tumour boards' (MTBs). Attended by a heterogenous set of practitioners, MTBs link genomic platforms to clinical practices by establishing 'actionable' connections between drugs and molecular alterations. Their activities rely on a number of evidential resources – for example databases, clinical trial results, basic knowledge about mutations and pathways – that need to be associated with the clinical trajectory of individual patients. Experts from various domains are required to master and align diverse kinds of information. However, rather than examining MTBs as an institution interfacing different kinds of expertise embedded in individual experts, we argue that expertise is the emergent outcome of MTBs, which can be conceptualised as networks or 'agencements' of humans and devices. Based on the ethnographic analysis of the activities of four clinical trial MTBs (three in France and an international one) and of two French routine‐care MTBs, the paper analyses how MTBs produce therapeutic decisions, centring on the new kind of expertise they engender. The development and activities of MTBs signal a profound transformation of the evidentiary basis and processes upon which biomedical expertise and decision‐making in oncology are predicated and, in particular, the emergence of a clinic of variants .